Divergent impacts on the gut microbiome and host metabolism induced by traditional Chinese Medicine with Cold or Hot properties in mice - Bingbing Li; Xin Tao; Lili Sheng; Yan Li; Ningning Zheng; Houkai Li (BMC, 2022)
Abstract Background Traditional Chinese Medicine (TCM) has been practiced and developed in China over thousands of years under the guidance of a series of complicated traditional theories. Herbs within TCM usually are classified according to their different properties ranging from cold, cool, warm to hot, which are simplified as Cold and Hot properties. TCM with either Cold or Hot properties are used in various formulae designed for the purpose of restoring the balance of patients. Emerging evidence has highlighted that an altered gut microbiota or host metabolism are critically involved in affecting the healing properties of TCM. However, at present the exact influences and crosstalk on the gut microbiota and host metabolism remain poorly understood. Methods In the present study, the divergent impacts of six TCMs with either Cold or Hot properties on gut microbiome and host metabolism during short- or long-term intervention in mice were investigated. Six typical TCMs with Hot or Cold properties including Cinnamomi Cortex (rougui, RG), Zingiberis Rhizoma (ganjiang, GJ), Aconiti Lateralis Radix Praeparata (fuzi, FZ), Rhei Radix et Rhizoma (dahuang, DH), Scutellariae Radix (huangqin, HQ), and Copitdis Rhizoma (huanglian, HL) were selected and orally administered to male C57BL/6J mice for a short- or a long-term (7 or 35 days). At the end of experiments, serum and cecal contents were collected for metabolomic and gut microbiome analyses using gas chromatography-tandem mass spectrometry (GC-MS) or 16S ribosomal deoxyribonucleic acid (16S rDNA) sequencing. Results The results revealed that the gut microbiome underwent divergent changes both in its composition and functions after short-term intervention with TCM possessing either Cold or Hot properties. Interestingly, the number of changed genus and bacteria pathways was reduced in Hot_LT, but was increased in Cold_LT, especially in the HL group. Increased α diversity and a reduced F/B ratio revealed the changes in Hot_ST, but a reduced Shannon index and increased altered bacteria function was evident in Cold_LT. The serum metabolic profile showed that the influence of TCM on host metabolism was gradually reduced over time. Glycolipid metabolism related pathways were specifically regulated by Hot_ST, but also surprisingly by Cold_LT. Reduced lactic acid in Cold_ST, increased tryptophan concentrations and decreased proline and threonine concentrations in Cold_LT perhaps highlighting the difference between the two natures influence on serum metabolism. These metabolites were closely correlated with altered gut microbiota shown by further correlation analyses. Conclusion The results indicated that TCM properties could be, at least partially characterized by an alteration in the gut microbiota and metabolic profile, implying that the divergent responses of gut microbiome and host metabolism are involved in different responses to TCM. Graphic Abstract